1998
DOI: 10.1001/jama.279.22.1801
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Socioeconomic and Cultural Factors on Racial Differences in Late-Stage Presentation of Breast Cancer

Abstract: Context.-Breast cancer mortality is higher among African American women than among white women in the United States, but the reasons for the racial difference are not known. Objective.-To evaluate the influence of socioeconomic and cultural factors on the racial difference in breast cancer stage at diagnosis. Design.-Case-control study of patients diagnosed as having breast cancer at the University Medical Center of Eastern Carolina from 1985 through 1992. Setting.-The major health care facility for 2 rural co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
411
2
13

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 586 publications
(441 citation statements)
references
References 43 publications
15
411
2
13
Order By: Relevance
“…48 Others have suggested that differential race effects on cancer treatment and outcomes are mediated by culturally based attitudes. 6 For instance, it is possible that the omission of radiation after breast conservation or the higher rates of mastectomy than breast conservation and radiation among black women may be due to culturally based attitudes toward radiation. Alternatively, unmeasured aspects of race-specific patient preferences may have contributed to our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Others have suggested that differential race effects on cancer treatment and outcomes are mediated by culturally based attitudes. 6 For instance, it is possible that the omission of radiation after breast conservation or the higher rates of mastectomy than breast conservation and radiation among black women may be due to culturally based attitudes toward radiation. Alternatively, unmeasured aspects of race-specific patient preferences may have contributed to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, rates failed to decline for older women, and older black women actually experienced an increase in mortality rates. [1][2][3] The observed excess mortality rates among older black women may be due to the interaction of several complex phenomena, including poverty, 4,5 culturally based attitudes, 6,7 bias in treatment, 5,8,9 stage at presentation, 10 -12 access to, or adequacy of treatment, 10,[13][14][15][16][17] tumor biology, 18 -23 and comorbid medical conditions. 24 In this study, data from a random sample of black and white Medicare beneficiaries treated in fee-forservice settings for local breast carcinoma are used to describe the associations between race and local treatment.…”
mentioning
confidence: 99%
“…Cultural barriers to care include language, religious beliefs, family ties, interactional styles, gender norms, and misconceptions about Western medicine [38]. Beliefs about cancer and its treatment may affect patients' willingness to seek screening tests and professional care [39]. Disparities have been identified in cancer screening tests [40] related to access to health care [41] and other factors [42].…”
Section: Cultural Barriers To Cancer Screening and Treatmentmentioning
confidence: 99%
“…More advanced stage at diagnosis is commonly found in developing countries [14], and is thought to be related to lack of universal coverage, lack of screening programs, and fear of cancer in general. Tumor size and stage decreased in the western world since the introduction of mammography in the Netherlands in the last decades of the twentieth century [16][17][18], and this went hand in hand with increased public awareness and reduced taboo status of the disease [19,20]. In Surinam, the vivid culture of traditional medicine and taboo status of BC, almost certainly, contribute to a more advanced stage at diagnosis.…”
Section: Survival In Monthsmentioning
confidence: 99%